THE EFFECT OF STEM INTEGRATED PHYSICS E-MODULES TO IMPROVE CRITICAL THINKING ABILITY OF CLASS XI STUDENTS OF SMAN 2 LUBUK SIKAPING - Elsa Fitriani; Festiyed Festiyed (Physics Learning and Education, 2023)
Life in this era of globalization requires many changes and developments from previous life. The methods and models used by teachers in the learning process also affect students' critical thinking skills. students' critical thinking, namely the discovery learning model with the STEM approach. The use of this model can change teacher centered learning to student centered. The teacher does not yet have access to references to the STEM learning approach which is accompanied by guidelines for use and the tools needed. Easy, namely less than 50%. The solution that can be done is to change the teaching materials used, namely can use STEM-integrated e-modules. The experimental class was given treatment in the form of STEM integrated e-modules, while the control class was not given treatment. After conducting the research it turned out that students' critical thinking abilities as seen from each student's answer from the two sample classes had different averages in common, namely the normality test, test homogeneity, two-mean similarity test From the analysis results obtained, namely the value of th is in the H0 resistance area so that it can be said that H1 is accepted at a significant level of 0.05. The results of the statistical analysis of the data show that th> tt is 5.897> 2.00, so it can be concluded that there are differences in students' critical thinking skills in the aspect of knowledge using e-modules and not using e-modules.